AN ANALYSIS OF TWO BIOACTIVE SECONDARY METABOLITES IN HARPAGOPHYTUM PROCUMBENS DC; HARPAGOSIDE AND VERBASCOSIDE IN VITRO AND IN VIVO - Wilson, G. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Extracts of Devils Claw (Harpagophytum procumbens, Pedaliaceae) are used widely for the relief of muscular pain. The vulnerability of wild plant populations of Harpagophytum to commercial harvesting of the tubers focuses attention on alternative methods of sustainable production of these bioactive compounds, such as the use of plant cell cultures The anti inflammatory activity has been attributed to free and glucoside forms of iridoid monoterpenes harpagoside, harpagide, procumbine and harpagogenine present in the tubers of the plant. There are, however, additional bioactive compounds present in Harpagophytum such as the caffoyl derivative verbascoside, reported to have anti-bacterial, anti-viral, anti-hypertensive and immunosuppressive properties. The purpose of this study was to compare the accumulation of these two classes of metabolites in cell suspension cultures and in hairy root cultures with that present in leaves and tubers from the intact plants. The results, based on spectroscopic analysis, show that harpagoside type compounds were almost undetectable in cell suspension or hairy root cultures (0.12mg.g-1 DW) compared to the plant (tuber 16.07mg.g-1 DW). However levels of verbascoside type compounds were similar in vitro (cell suspension 0.078g. g-1 DW) to the plant (tubers 0.056g. g-1 DW). It is clear that in these in vitro conditions cultures of cells or roots of Harpagophytum procumbens lack a complete biosynthetic pathway for iridoid glycoside biosynthesis. However the caffoyl derivatives, verbascoside type compounds, are accumulated substantially. Taken together, in vitro produced material contains a markedly different profile of bioactive compounds compared to that present in the intact plant.